2012
DOI: 10.1039/c2nr11489e
|View full text |Cite
|
Sign up to set email alerts
|

Fe3O4/Au/Fe3O4nanoflowers exhibiting tunable saturation magnetization and enhanced bioconjugation

Abstract: Composite nanoparticles have proved to be promising in a wide range of biotechnological applications. In this paper, we report on a facile method to synthesize novel Fe(3)O(4)/Au/Fe(3)O(4) nanoparticles (nanoflowers) that integrate hybrid components and surface types. We demonstrate that relative to conventional nanoparticles with core/shell configuration, such nanoflowers not only retain their surface plasmon property but also allow for 170% increase in the saturation magnetization and 23% increase in the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 41 publications
0
34
0
Order By: Relevance
“…The different structures with core/shell, dumbbell-like and flower-shape of these nanoparticles have been reported. [27][28][29] Herein, the Fe 3 O 4 /Au/Fe 3 O 4 configuration (nanoflowers) with 38 nm diameter was synthesized 30 and used as a carrier to set up a device for SNP detection. Compared to other matrix nanoparticles, our patented PAA ( poly-acrylic acid) modification of GoldMag nanoparticles ensures the significantly elevated stableness and compatibility of the particles for biological interactions.…”
Section: Introductionmentioning
confidence: 99%
“…The different structures with core/shell, dumbbell-like and flower-shape of these nanoparticles have been reported. [27][28][29] Herein, the Fe 3 O 4 /Au/Fe 3 O 4 configuration (nanoflowers) with 38 nm diameter was synthesized 30 and used as a carrier to set up a device for SNP detection. Compared to other matrix nanoparticles, our patented PAA ( poly-acrylic acid) modification of GoldMag nanoparticles ensures the significantly elevated stableness and compatibility of the particles for biological interactions.…”
Section: Introductionmentioning
confidence: 99%
“…GoldMag nanoparticles were synthesized and characterized as described previously (21). The general scheme to functionalize nanoflower GMNs with CTAB and PSS coating, is represented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…GoldMag nanoparticles (5 mg/ml) with a nanoflower structure (21) and lateral flow strips were provided by Xi'an GoldMag Nanobiotech Co., Ltd. (Xi'an, China). Buffers were prepared according to standard laboratory procedures.…”
Section: Methodsmentioning
confidence: 99%
“…97 The dendritic Fe 3 O 4 @Au NPs show a mean particle size of 35 nm, intense near-infrared (NIR) absorbance at 754 nm, and strong superparamagnetism, implying the potential applications in the fields of the optical/magnetic-resonance bimodal imaging, photothermal-magnetothermal combined therapy, low temperature catalysis, and magnetic separation. Hui et al 98 reported a convenient method for synthesis of novel Fe 3 O 4 @Au@Fe 3 O 4 nanoflowers that integrate hybrid components and surface structures. Relative to conventional NPs with the core-shell configuration, such nanoflowers not only retain their surface plasmon properties but also allow for a 170% increase in the saturation magnetization and a 23% increase in the conjugation efficiency because of the synergistic cooperation among the hierarchical structures.…”
Section: Structure and Synthesis Of Magnetoplasmonic Nanoparticlesmentioning
confidence: 99%